Microbubbles Contrast Agents: General Overview as Diagnostics and Therapeutic Agent - Gharat, Shivani K.; Godiyal, Shilpa C.; Malusare, Pranali P.; Jadhav, Kisan R.; Kadam, Vilasrao J. (Current Drug Targets, 2022)
Recent discoveries have unfolded many powerful emerging applications in the field of drug delivery science. For the past few years, ultrasound mediated microbubble contrast agents have been an emerging modality for diagnostic and drug delivery applications. Microbubbles are small spherical bubbles composed of a gas core encapsulated by a shell with different materials. The composition of the microbubble determines its stiffness, encapsulation efficiency, stability, and clearance from the system. A gas-filled microbubble, when activated by an acoustic pulse, can produce large volumetric oscillations and, once administered intravenously, can act as a cavitating nuclei, allowing for a wide range of ultrasound-assisted drug delivery applications. Microbubbles offer a fantastic approach to ultrasound triggered drug delivery with various drug loading techniques and targeting strategies for the uptake of bioactive substances such as polynucleotides, proteins, genes, and small-molecule drugs. Microbubbles can be used for several diagnostic and therapeutic purposes for accurate detection and treatment of various life-threatening diseases.
Keywords: cavitation nuclei